2008
DOI: 10.1021/om7007937
|View full text |Cite
|
Sign up to set email alerts
|

A-Frame Complexes of Dirhodium Bridged by Dicarbene and Diphosphine Ligands

Abstract: The complexes [RhBr(COD)]2(μ-di-NHC), in which di-NHC represents the di-N-heterocyclic carbenes MeCCmeth (1,1′-methylene-3,3′-dimethyldiimidazol-2,2′-diylidene), tBuCCmeth (1,1′-methylene-3,3′-di-tert-butyldiimidazol-2,2′-diylidene), and MeCCeth (1,2-ethylene-3,3′-dimethyldiimidazol-2,2′-diylidene), have been prepared from the reactions of the corresponding diimidazolium bromide salts with the acetate-bridged complex [Rh(μ-OAc)(COD)]2. The analogous complex containing the tBuCCeth group (1,2-ethylene-3,3′-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 72 publications
4
29
0
Order By: Relevance
“…The 1 H NMR spectral parameters for the series of complexes (2c and 2d) are closely comparable to those described for 2b 46 and also to those of previously reported pendent complexes involving other metals. 18,31,67,81-89 Complexes 2b-2d show typical resonances for the coordinated COD ligands (between d 1.7 and d 5.7) as given in the Experimental section.…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…The 1 H NMR spectral parameters for the series of complexes (2c and 2d) are closely comparable to those described for 2b 46 and also to those of previously reported pendent complexes involving other metals. 18,31,67,81-89 Complexes 2b-2d show typical resonances for the coordinated COD ligands (between d 1.7 and d 5.7) as given in the Experimental section.…”
Section: Methodssupporting
confidence: 84%
“…Most often, single deprotonation of the diimidazolium salts is carried out using complexes containing basic ligands such as acetate or methoxide groups, which serve to deprotonate these salts. This is the method used with some success in this report, and in previous reports by us 46 and others. 18,31,46,81-84 ,86-88, [90][91][92][93] In a previous study we had shown that the acetate-bridged complex, [Rh(m-OAc)(COD)] 2 , was effective in the deprotonation of a number of diimidazolium salts generating the corresponding series of di-NHC-bridged dirhodium products.…”
Section: Methodssupporting
confidence: 65%
See 3 more Smart Citations